Singapore And Sustainable Finance: Successful Models In Policy Implementation And Best Practices, Compare With Indonesia - Fadhillah, Fadhillah; Agung, Wahyu Dwi (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2024)
Singapore stands out among ASEAN countries for its notable accomplishments in sustainable finance. Singapore is the sole ASEAN country featured in the top 15 rankings of the thirteenth edition of the Global Green Finance Index. Therefore This study aims to find the determining factors for Singapore's success in the implementation of sustainable finance. This research uses qualitative methods and literature review approaches. Upon examining the reports and official websites from the Financial Services Authority (OJK) (Indonesia) and the Monetary Authority of Singapore (MAS) (Singapore), it is evident that Singapore has implemented similar initiatives as Indonesia in addressing its three key issues; lack of knowledge and involvement in the financial sector, standardization of green categorization, and support and collaboration for business opportunities. Both countries have implemented national campaigns, published green taxonomies, and fostered public-private partnership to address these issues. In this study, a new finding was revealed in terms of culture financial understanding. Singapore lacks particular rules pertaining to the promotion of financial literacy. However, Singapore boasts a far greater financial literacy rate compared to other ASEAN countries. The high level of financial literacy certainly has positive influences on the implementation of sustainable finance. Singapura menjadi negara ASEAN terbaik karena prestasinya dalam hal keuangan berkelanjutan. Singapura adalah satu-satunya negara ASEAN yang masuk ke dalam peringkat 15 besar berdasarkan Global Green Finance Index edisi ketiga belas. Penelitian ini bertujuan untuk menemukan faktor penentu kesuksesan Singapura dalam implementasi keuangan berkelanjutan. Penelitian ini menggunakan metode kualitatif dan pendekatan literatur rview. Berdasarkan laporan dan situs web resmi dari Otoritas Jasa Keuangan (OJK) (Indonesia) dan Otoritas Moneter Singapura (MAS) (Singapura) terbukti bahwa Singapura telah menerapkan strategi serupa seperti Indonesia dalam mengatasi tiga masalah utamanya; kurangnya pengetahuan dan keterlibatan di sektor keuangan, standardisasi kategori hijau, serta dukungan dan kolaborasi untuk peluang bisnis. Kedua negara tersebut telah menerapkan kampanye nasional, menerbitkan taksonomi hijau, dan membina kemitraan publik-swasta untuk mengatasi masalah ini. Dalam penelitian ini, sebuah temuan baru terungkap dalam hal budaya terkait pemahaman keuangan. Singapura tidak memiliki aturan khusus yang berkaitan dengan promosi literasi keuangan. Namun, Singapura memiliki tingkat literasi keuangan yang jauh lebih besar dibandingkan dengan negara ASEAN lainnya. Tingginya tingkat literasi keuangan tentunya memberikan pengaruh positif terhadap penerapan keuangan berkelanjutan.